Application of Box method for multi-objective optimization problems - Данилкович, Анатолій Григорович; Брановицька, Слава Вікторівна; Бондаренко, Сергій Григорович; Сангінова, Ольга Вікторівна (Eastern-European Journal of Enterprise Technologies, 2013)
The article presents a criterion of optimality in the form of a generalized additive objective function to optimize the chrome tanning of the semi-finished product. Local criteria of the objective function are normalized and reduced to dimensionless form. Weight factors are obtained on the bases of expert assessments. To solve the problem of multi-objective optimization a complex Box method was used. The algorithm of the Box method serves as a basis for the software module, which is implemented using object-oriented programming language Visual Basic for Application. The software module provides an opportunity to work with explicit and implicit restrictions. The developed software module was used to find the optimal values of the generalized objective function. For low-waste technology of tanning of semi-finished product with dry chrome tanning agent we obtained its mathematical description and determined restrictions on technological parameters of the process. The problem of optimization of the process of dry chrome tanning of semi-finished product was solved and the optimal values of the parameters of the process of tanning were determined